Teen Fertility and Labor Market Segmentation: Evidence from Madagascar - Catalina Herrera; David E. Sahn; Kira M. Villa (Institute of Labor Economics (IZA), 2016)
Women represent the majority of informal sector workers in developing countries, especially in Sub-Saharan Africa where adolescent pregnancy rates are high. Little empirical evidence exists concerning the relationship between teen fertility and the likelihood that a woman will be employed in the informal sector. Using a panel survey in Madagascar designed to capture the transition from adolescence to adulthood, we estimate a multinomial logit model to capture the effect of the timing of first birth on female selection into four categories: non-participation, informal, formal, and student. To address the endogeneity of fertility and labor market outcomes, we instrument the timing of first birth using young women's community-level access, and duration of exposure to family planning. Our results suggest that motherhood increases the probability of employment for young women and that women whose first birth occurs during adolescence largely select into low-quality informal jobs. This effect is partially, but not entirely, mediated by the effect of teen pregnancy on schooling.
Keywords: J13; J24; O1; 330; fertility; informal sector; adolescence; female labor force participation; Madagascar